2006
DOI: 10.1128/aem.02771-05
|View full text |Cite
|
Sign up to set email alerts
|

Succession of Bacterial Communities during Early Plant Development: Transition from Seed to Root and Effect of Compost Amendment

Abstract: Compost amendments to soils and potting mixes are routinely applied to improve soil fertility and plant growth and health. These amendments, which contain high levels of organic matter and microbial cells, can influence microbial communities associated with plants grown in such soils. The purpose of this study was to follow the bacterial community compositions of seed and subsequent root surfaces in the presence and absence of compost in the potting mix. The bacterial community compositions of potting mixes, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 49 publications
7
67
0
1
Order By: Relevance
“…With increasing proximity to the root, we observed a strong rhizosphere effect, and that the plant influence on bacteria from the genus Streptomyces predominated over soil and compost effects (Inbar et al, 2005). In a more general analysis of bacterial communities associated with plant seeds and roots, we observed that while seed surfaces were largely colonized by dominant potting mix populations, root microbial communities differed significantly from the source potting mix communities (Green et al, 2006). However, despite a general divergence between the community composition of seed and root bacteria, two distinct taxonomic groups were consistently detected in seed and root communities.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…With increasing proximity to the root, we observed a strong rhizosphere effect, and that the plant influence on bacteria from the genus Streptomyces predominated over soil and compost effects (Inbar et al, 2005). In a more general analysis of bacterial communities associated with plant seeds and roots, we observed that while seed surfaces were largely colonized by dominant potting mix populations, root microbial communities differed significantly from the source potting mix communities (Green et al, 2006). However, despite a general divergence between the community composition of seed and root bacteria, two distinct taxonomic groups were consistently detected in seed and root communities.…”
Section: Introductionmentioning
confidence: 74%
“…Plant growth sampling and DNA extraction Cucumber seeds (Cucumis sativus L. 'straight eight') were sown in three peat-based potting mixes amended with composts, as previously described (Green et al, 2006). The two composts employed were sawdust-amended ('sawdust compost') and straw-amended ('straw compost') cow manure composts, as previously described (Changa et al, 2003;Green et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations